An Eleven Year Old Boy with Drug Rash with Eosinophilia and Systemic Symptoms (DRESS) - Desy Wulandari; Wisnu Barlianto; Nisak Humairok (Medical Faculty of Brawijaya University, Indonesia, 2022)
Introduction: The prospective studies have estimated that the DRESS syndrome incidence rate is about 1 per 1000 to 10,000 with the mortality rate is to be around 10% to 20%. Case: We have been reported a case of DRESS in an eleven-year-old boy who came to the emergency room with the chief complaint of maculopapular rash in the body that had been happened for three days. The rash was first appeared in the arms area and thus spread to the trunk, abdomen, and lower extremities. The erythema was well-demarcated, purplish in color. There was a history of fever a week before admission which reached 40 0 Celcius. There are multiple histories of drug administration, either orally or intravenously to this patient, and made the diagnosis of drug reaction is highly possible. The management of these patients consists of suspending suspected drugs and implementing supportive measures. Conclusion: Regarding pharmacological treatment, the use of systemic corticosteroids for a prolonged period with a gradual decrease is suggested, to avoid relapses.